(untitled) (Portuguese Journal of Family Medicine and General Practice, 2023)
Introduction: Angiosarcoma is a rare vascular neoplasm, but with high aggressiveness with high rates of local recurrence and early metastasis. Clinically, it can be confused with simple hematomas or other infectious and inflammatory diseases, often making early diagnosis difficult. Skin biopsy plays a key role. Case description: We describe the case of a 70-year-old man, leukodermic, with the appearance of a spot in the left eye after two months of evolution, initially in the pre-auricular region with progression to the periocular area; no trauma associated. The patient was referred to a dermatology consultation, having performed a skin biopsy, revealing that it was an advanced epithelioid angiosarcoma of the face. He was followed up in oncology, having undergone a cycle of chemotherapy treatments with pegylated liposomal doxorubicin, showing a favorable evolution of the lesion with no evidence of metastasis until now. Comment: Early recognition of this type of neoplasm is essential, and the clinician should be diligent in relation to some aspects such as the appearance of skin spots on the face as well as ulcers or skin wounds that do not heal after four to six weeks, allowing a positive impact on the prognosis.